2019
DOI: 10.1155/2019/3206542
|View full text |Cite
|
Sign up to set email alerts
|

Bailcalin Protects against Diabetic Cardiomyopathy through Keap1/Nrf2/AMPK-Mediated Antioxidative and Lipid-Lowering Effects

Abstract: Previous studies demonstrated that Bailcalin (BAI) prevented cardiac injuries under different disease models. Whether BAI protected against type 2 diabetes mellitus- (T2DM-) associated cardiomyopathy was investigated in this study. T2DM was established by the combination of streptozotocin injection and high-fat diet in mice. BAI was administered daily for 6 months. After evaluating cardiac functions, mice hearts were removed and processed for morphological, biochemical, and molecular mechanism analyses. Neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…In the cardiac tissue, similarly to the serum, the activity of antioxidative enzymes was elevated. These results are in line with some other reports [26,61], but there are also reports indicating a decrease in antioxidative enzymes activity in the heart of diabetic animals [24,33,58,62]. In the study conducted by Okutan et al regarding the effect of caffeic acid phenethyl ester on oxidative stress markers in the heart it was shown that similarly to our results, the activities of SOD and CAT were elevated in diabetic rats, while GPx activity was unchanged when compared to the non-diabetic animals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the cardiac tissue, similarly to the serum, the activity of antioxidative enzymes was elevated. These results are in line with some other reports [26,61], but there are also reports indicating a decrease in antioxidative enzymes activity in the heart of diabetic animals [24,33,58,62]. In the study conducted by Okutan et al regarding the effect of caffeic acid phenethyl ester on oxidative stress markers in the heart it was shown that similarly to our results, the activities of SOD and CAT were elevated in diabetic rats, while GPx activity was unchanged when compared to the non-diabetic animals.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it can be concluded, that the model reflecting the changes observed in the type 2 diabetes in humans in the most adequate manner is a model in which a high-fat diet is combined with a single injection of a low dose of streptozotocin [52,53]. It should be noted that the majority of studies describing the effect of tested substances on parameters affected by both the type 1 and type 2 diabetes is based on the experiments conducted on male laboratory animals [17,[19][20][21][22][23][24][25][32][33][34][35]37,38,50,51,[54][55][56][57][58][59][60][61][62]. Following the suggestion of The National Institutes of Health (NIH) to use female animals in the laboratory studies [63] and reports about sex-dependent metabolic differences [64,65], our experiment was conducted on female rats.…”
Section: Discussionmentioning
confidence: 99%
“…As for Nrf2, another vital antioxidant sensor, it confers maintenance of cellular defense system by promoting the expressions of antioxidant molecules when its position shifts from the cytoplasm to the nucleus where it binds to AREs [ 55 , 56 ]. Many previous studies have already revealed the two redox-sensitive proteins closely implicated in the therapeutic effects on diabetic cardiomyopathy [ 21 , 46 , 57 , 58 ]. More importantly, SIRT1 is involved in the regulation and control of oxidative stress that are associated with diverse stimulus, which appears to be exerted by activating Nrf2, indicating that Nrf2 serves as an important downstream target of SIRT1 signaling [ 25 , 26 , 31 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the important pathological structural changes in diabetes is myocardial fibrosis (15,16). TGF-β1 signaling pathway is activated by continuous of hyperglycemia and then increased the level of fibrotic markers in hearts of diabetic mice, including α-SMA, Col I, and Col III (17).…”
Section: Discussionmentioning
confidence: 99%